UPAYA MENINGKATKAN KEBERHASILAN IMPLEMENTASI ERP UNTUK MEMBANGUN KEUNGGULAN BERSAING UKM DI JAWA TENGAH (Jurnal Manajemen dan Kewirausahaan, 2013)
Enterprise Resource Planning is an integrated software applied in the organization. This study aimed to determine the factors that influence the successful implementation of ERP in Small and Medium Enterprises (SMEs) in Central Java to build competitive advantage. The hypothesis were tested by SEM to 107 respondents. Results of data analysis proved that the variable Business Process Reengineering was the most impact. It recommended that small and medium entrepreneurs to learn and consolidate prior efforts to reengineer its business before applying ERP.